2022
DOI: 10.3390/jcs6070190
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sensor Position and Low-Frequency Modal Shape on the Sensitivity of Vibro-Acoustic Modulation for Impact Damage Detection in Composite Materials

Abstract: Very sensitive structural health monitoring methods are needed to detect barely visible impact damage in composite materials. Based on extracting non-linear modulated components from the frequency response of the damaged system, vibro-acoustic modulation (VAM) has shown to be effective in identifying the presence of damage at its early stage. A decisive role in the success of this technique is played by the choice of the high-frequency probe and the low-frequency pump sinusoidal signals that simultaneously exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For example, for the pump amplitude of 250 mVpp and the range 240-360 Hz, sidebands do not emerge when the sensor is in position S2 (figure 12b), while they are evident for sensor location S1 (figure 10b). The effect of the position of the sensor on the modulation intensity was investigated in other studies and was seen to depend on the distance of the sensor location from the nodal points of the deformed beam at the excitation frequency [39].…”
Section: Nonlinear Vibro-acoustic Modulation Tests and Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, for the pump amplitude of 250 mVpp and the range 240-360 Hz, sidebands do not emerge when the sensor is in position S2 (figure 12b), while they are evident for sensor location S1 (figure 10b). The effect of the position of the sensor on the modulation intensity was investigated in other studies and was seen to depend on the distance of the sensor location from the nodal points of the deformed beam at the excitation frequency [39].…”
Section: Nonlinear Vibro-acoustic Modulation Tests and Resultsmentioning
confidence: 95%
“…They showed that the perturbation introduced in the cracked region and, thus, the modulation intensity, greatly depends on the applied vibration mode. More recently, the VAM technique was used by the authors with a multi-modal pump excitation to detect barely visible damage in a composite beam [39]. The method was found to be effective, though affected by the position of the sensor with respect to the bending shape of the selected pump frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of sidebands in the response signal indicates the existence of damage in the structure. 103 The applications of Vibro-acoustic modulation include the detection of cracks in metallic plates, 104,105 bond strength detection in composites, 106 delaminations in composite laminates, 107 impact damage in laminated composites, 108,109 looseness in bolted joints, 110 etc. In bolted joints, Impact modulation, and Vibro modulation are two extensively used Vibro-acoustic modulation techniques for looseness detection.…”
Section: Overview Of Traditional Methods For Looseness Detection Of B...mentioning
confidence: 99%